Isolation and characterization of indigenous Streptomyces and Lentzea strains from soils containing boron compounds in Argentina - Moraga, Norma Beatriz (2013)
The Salta Province in the northwest of Argentina is the main worldwide producer of hydroboracite and leads in exports of boron mineral and its derivatives in Latin America. In addition to the natural presence of boron compounds in the soils, there are others contaminated due to the boron mining industry. Although some bacteria are known to require boron for their growth or to be capable of storing boron, no studies have been published about Streptomyces or Lentzea generas capacity to tolerate high boron concentrations, or about theirmetabolic capacities in boron contaminated environments. The results of this research showthe isolation andmolecular characterization of eight strains belonging to the Actinobacteria phylum collected from different soils contaminated with high boron concentration in Salta state. The boron tolerance assays, which show that three of the strains were able to tolerate up 60/80 mMboron, demonstrate the potential capability of this group of bacteria to grow and maybe to remove boron from the environment. They appear to be promising, considering that thesemicroorganisms are infrequent pathogens, are metabolically versatile and many Streptomyces can synthesize boron containing metabolites.